Art and libraries in Iceland - Arnadottir, Arndis S. (Art Libraries Journal, 1987)
Iceland’s cultural heritage dates back to the Vikings. While crafts have always been important to the Icelandic way of life, the country has become much more art and design conscious with the development of educational and cultural institutions in the last hundred years. The National Library receives copies of all Icelandic publications and publishes the Icelandic national bibliography (which includes art but omits some exhibition catalogues); in addition the Library of the National Gallery collects all published literature on Icelandic art. There is a major art collection in the University Library and a specialist art library at the Icelandic College of Arts and Crafts. The Nordic House at Reykjavίk accommodates an artotek. Because of its isolation, Iceland is unusually dependent on libraries for knowledge of world art, and much work remains to be done on the bibliography of Icelandic art. However, art librarianship has made substantial progress since the 1970s, and training in art librarianship is available.